Determinan Kecelakaan Kerja Pada Industri Kapal Pinisi : Studi Cross-Sectional di Kabupaten Bulukumba - Hidayat Hidayat; Hamsir Ahmad; Erwinda Alwi Rachman; Pius Kopong Tokang; Syahla Jeknour Saputri (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2026)
The traditional Pinisi shipbuilding in Bulukumba Regency is known as a valuable maritime cultural heritage, but faces major challenges in terms of occupational safety. This study aims to determine the factors related to the occurrence of work accidents in shipbuilding workers. This study used a quantitative approach with a cross-sectional design, involving 109 respondents selected using the Slovin formula. Data were collected through questionnaires and direct measurements using a Sound Level Meter and Hygrometer.The results showed that 56 respondents (51.4%) had experienced work accidents. The results of the Chi-Square test showed that the variables of age (p = 0.000), education level (p = 0.001), length of service (p = 0.029), length of service (p = 0.302), use of PPE (P = 0.004), noise (p = 0.624), and air temperature in the work area that had been measured from six points had an average temperature of 31.33ºC. Based on the results of the study, it can be concluded that there is a relationship between age, length of service, education level, use of PPE, and air temperature with the occurrence of work accidents, while there is no relationship between length of service, and noise with the occurrence of work accidents. Efforts are needed to increase awareness and implementation of K3 and the provision of adequate PPE to reduce the number of work accidents.